PENGARUH TERHADAP KEPUTUSAN PEMBELIAN PRODUK FAST MOVING CONSUMER GOODS UNILEVER - Yundira, Viska; Kumala, Destiana; Ferdinand, Novingky (Program Studi Ekonomi Syariah, 2025)
Unilever is facing reputation challenges due to its association with conflict countries and its involvement in environmental pollution. This has led to a decrease in consumer interest. In order to address these issues and develop effective marketing strategies, a study was conducted using a quantitative approach, focusing on green marketing and Islamic advertising. The research included 68 respondents who completed questionnaires using Likert scales. The results, analyzed using the SPSS program, showed that both green marketing and Islamic advertising have a significant and positive impact on purchasing decisions, both individually and together. The study found that 60.6% of purchasing decisions can be attributed to green marketing and Islamic advertising, while the remaining 39.4% is influenced by other factors not examined in this research. Furthermore, Islamic advertising was identified as the most influential variable on purchasing decisions for Unilever's fast-moving consumer goods products in the Bogor Regency